Thrombin Induces Secretion of Multiple Cytokines and Expression of Protease-Activated Receptors in Mouse Mast Cell Line - Fang, Xiaobin; Liao, Ren; Yu, Yingyan; Li, Jingyi; Guo, Zaipei; Zhu, Tao (Mediators of Inflammation, 2019)
Background. Thrombin could elicit degranulation of mast cells involved in numerous physiologic and pathologic processes; however, the detailed scrutiny of this procedure and further research of possible cell signaling pathways are lacking. Methods. P815 mouse mast cells were exposed to various concentrations of thrombin for 16 h. Expression of protease-activated receptor (PAR)1, PAR2, PAR3, and PAR4 mRNA in P815 was analyzed by quantitative real-time PCR (qRT-PCR) and the fittest concentration of thrombin was decided. Then, secretions of mediators from P815 stimulated by thrombin 0.2 U/ml were determined using enzyme-linked immunosorbent assay (ELISA) and Luminex liquichip; the possible cell signaling pathways were measured by immunoblotting. Furthermore, inhibition of thrombin inhibitor (hirudin), PAR1 inhibitor (SCH79797), and MAPK inhibitors (SB203580, PD98059, and SP600125) on the mediator section was evaluated by ELISA and Luminex liquichip. Results. Thrombin 0.2 U/ml induced the elevated expression of PAR1, PAR2, PAR3, and PAR4, as well as the increasing level of phospho-IκBα, phospho-SAPK/JNK MAPK, phospho-P38 MAPK (Thr180/Tyr182), and phospho-ERK1/2 MAPK (p44/42) in P815. Secretion of vascular endothelial growth factor (VEGF), tumor necrosis factor-α (TNF-α), interleukin- (IL-) 2, IL-6, chemokine ligand- (CCL-) 2, chemokine (C-X-C motif) ligand- (CXCL-) 1, and CXCL-5 from P815 increased apparently; this effect could be diminished by hirudin, whereas SCH79797 and MAPK inhibitors (SB203580, PD98059, and SP600125) diminish the secretions with weaker effect. Conclusion. We found the expression of PAR mRNA in P815, activation of signaling pathways of nuclear factor-kappaB (NF-κB), and mitogen-activated protein kinases (MAPKs) including C-Jun NH2-terminal kinase (JNK), P38, and extracellular signal-regulated kinase 1/2 (ERK1/2), and the release of multiple inflammatory mediators stimulated by thrombin, as well as the inhibition of the inflammatory releases by hirudin, SCH79797, and MAPK inhibitors including SB203580, PD98059, and SP600125.